2020
DOI: 10.7759/cureus.10739
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Tonsil Causing Small Bowel Perforation in the Setting of Metastasis and Treatment With Programmed Death-1 Inhibitors: A Case Report

Abstract: Metastasis of extra-intestinal carcinoma to the gastrointestinal tract (GIT) is a rare event, most commonly occurring with malignant melanoma. Anti-PD-1 (programmed death-1) immunotherapeutic agents are immune checkpoint inhibitors with proven benefit across multiple cancer types, including squamous cell carcinoma of the head and neck (SCCHN). Here we describe a case of small bowel perforation attributed to a primary SCCHN metastasizing to the GIT in the setting of treatment with PD-1 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…GIP signals associated with ICIs were detected by using the VigiBase database that confirmed our research (47). More and more studies reported cases of GIP after taking PD-1 (48,49). Therefore, these signals need to be paid more attention.…”
Section: Journal Of Pharmacy and Pharmaceutical Sciencessupporting
confidence: 80%
“…GIP signals associated with ICIs were detected by using the VigiBase database that confirmed our research (47). More and more studies reported cases of GIP after taking PD-1 (48,49). Therefore, these signals need to be paid more attention.…”
Section: Journal Of Pharmacy and Pharmaceutical Sciencessupporting
confidence: 80%
“…13 Metastases present primarily as obstructions but can also present as ileus, hemorrhage, bowel perforation, melena, and obstructive jaundice. [2][3][4][5][6][7][8][9][10][11]14 The initial evaluation of small bowel metastasis starts with CTs, magnetic resonance imagings, or PET scans. 3 Diagnosis is confirmed by obtaining pathology from upper endoscopy, enteroscopy, or exploratory laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been approximately 22 reported cases of head and neck cancers with metastasis to the bowel. [2][3][4][5][6][7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%